1980
DOI: 10.1161/01.cir.61.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide and hemodynamic assessment of left ventricular functional reserve in patients with left ventricular aneurysm and congestive cardiac failure. Response to exercise stress and isosorbide dinitrate.

Abstract: The hemodynamic response to exercise stress was assessed in 17 patients with left ventricular (LV) aneurysm, demonstrated by contrast left ventriculography, and congestive cardiac failure (CCF) before and after sublingual isosorbide dinitrate (ISDN). Radionuclide ventriculography was performed at rest and during exercise in 14 patients. ISDN increased mean exercise LV stroke work index (LVSWI) from 31 to 39 g-m/m2 (p less than 0.001) and reduced mean exercise LV filling pressure from 38 to 25 mm Hg (p less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Thus, the overall yield in detecting resectable aneurysms is very low, even in those patients with poor left ventricular function. It is interesting to note that in our patients with resectable ventricular aneurysms and those patients reported by Rogers et a1 [19] and Stephens et a1 [20], the left ventricular ejection fraction was in the range of 20-30%.…”
Section: Discussionsupporting
confidence: 60%
“…Thus, the overall yield in detecting resectable aneurysms is very low, even in those patients with poor left ventricular function. It is interesting to note that in our patients with resectable ventricular aneurysms and those patients reported by Rogers et a1 [19] and Stephens et a1 [20], the left ventricular ejection fraction was in the range of 20-30%.…”
Section: Discussionsupporting
confidence: 60%
“…Differences in functional reserve of the contractile segment might to some extent account for such behaviour. Stephens et al (25) found that a rest segmental EF (sEF) less than 40% usually predicts a poor left contractile reserve, while the opposite is not always true of patients with a sEF over 40%. It appears then that other factors besides the rest sEF play some role in determining left ventricular response to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…It appears then that other factors besides the rest sEF play some role in determining left ventricular response to exercise. The degree of coexisting coronary artery disease has been shown to be of little predictive value since its severity does not correlate with poor left ventricular response (25). The ventricular response to submaximal exercise is most likely conditioned also by the direct effects of the aneurysm on ventricular mechanics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we performed a subgroup analysis of patients with available LVEDP. For this analysis, LVSWI was calculated as 0.0136*SVI*(MAP + dp mean − LVEDP) 21 …”
Section: Methodsmentioning
confidence: 99%